Biomechanical analysis of free shooting technique in basketball in relation to precision and position of the players - Stankovic, R.; Simonovic, C.; Herodek, K. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
On a representative sample of subjects - basketball players of the basketball club -Zdravlje- from Leskovac playing on different positions as guard, forward and center - a video recording of the free throws technique was made with the aim to define the differences in kinematic and goniometric parameters related to the success in free throw realization. By means of 2D kinematic analysis 120 attempts of free throws were encompassed and they were categorized as successful, successful with overthrow, successful with underthrow and unsuccessful. The results were statistically processed by: means of the multivariate variant analysis. It was obtained the following: researched kinematic and gonimetric parameters differ statistically in a significant manner depending on the success of the free throw technique in basketball.